The information content in the offshore Renminbi foreign-exchange option market: Analytics and implied USD/CNH densities - Michael Funke; Julius Loermann; Andrew Tsang (Bank of Finland, Institute for Economies in Transition (BOFIT), 2017)
In line with the deepening of the derivative foreign-exchange market in Hong Kong, we recover risk-neutral probability densities for future US dollar/offshore renminbi exchange rates as implied by exchange rate option prices. The risk-neutral densities (RND) approach is shown to be useful in analyzing market sentiment and risk aversion in the renminbi market. We include a forecasting exercise that confirms market participants were able to forecast the shape of the actual densities correctly for short horizons, even if their exact location could not be determined.
URN:NBN:fi:bof-201710241649
Keywords: C53; F31; F37; 330